2014
DOI: 10.1186/1472-6823-14-64
|View full text |Cite
|
Sign up to set email alerts
|

Chromogranin A is a reliable serum diagnostic biomarker for pancreatic neuroendocrine tumors but not for insulinomas

Abstract: BackgroundPancreatic neuroendocrine tumors (PNETs) are a group of rare tumors. Chromogranin A (CgA) was considered as the most practical and useful serum tumor marker in PNET patients. But peripheral blood levels of CgA are not routinely tested in Chinese patients with PNETs. This study was to assess the diagnostic value of CgA in Chinese patients with PNETs especially in patients with insulinomas.MethodsEighty-nine patients with PNETs including 57 insulinomas and 32 non-insulinoma PNETs as well as 86 healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 53 publications
3
35
0
5
Order By: Relevance
“…In contrast to other pNETs a recent study reports that evaluation of serum CgA levels are frequently not helpful for diagnosing patients with insulinoma, with an elevated CgA value having only a 73% specificity compared with 92% in non-insulinoma p-NET patients [86]. …”
Section: Diagnosis Of F-p-nets and Nf-p-netsmentioning
confidence: 99%
“…In contrast to other pNETs a recent study reports that evaluation of serum CgA levels are frequently not helpful for diagnosing patients with insulinoma, with an elevated CgA value having only a 73% specificity compared with 92% in non-insulinoma p-NET patients [86]. …”
Section: Diagnosis Of F-p-nets and Nf-p-netsmentioning
confidence: 99%
“…Chromogranin A and neuron-specific enolase are used in diagnostic and follow up by pancreatic neuroendocrine neoplasms. Despite their reliability some studies showed that insulinoma cells do not secrete chromogranin A and neuron specific enolase into the circulation and therefore these markers are not suitable for diagnostic purposes by insulinomas [43,44]. Dynamic tests with tolbutamid, insulin or secretin are not commonly used.…”
Section: Laboratorymentioning
confidence: 99%
“…CgA has been documented to have modest value in the diagnosis of sporadic PNETs, with an overall sensitivity ranging from 53·6% to 77·0% and a specificity between 56·0% and 91·9%. Based on these findings, CgA has been recommended by the recent European Neuroendocrine Tumor Society (ENETS) and North American Neuroendocrine Tumor Society (NANETS) guidelines as the most practical and useful serum tumour marker for sporadic PNET diagnosis .…”
Section: Introductionmentioning
confidence: 99%